2004
DOI: 10.1002/ar.a.20141
|View full text |Cite
|
Sign up to set email alerts
|

Torsional resistance as a principal component of the structural design of long bones: Comparative multivariate evidence in birds

Abstract: Here we study the occurrence of torsion-resisting morphological and histological features (thin bone walls, circular shaft cross-section, oblique collagen fibers, and laminar tissue arrangement) in a sample of 168 long bones from wings and legs of 22 bird species. These structural parameters were measured in mid diaphyseal undemineralized cross-sections and analyzed using uni-, bi-, and multivariate (principal components analysis) data analysis techniques. We found that the four variables are significantly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(174 citation statements)
references
References 64 publications
10
157
2
5
Order By: Relevance
“…Instead, avian hindlimb bones have often been assumed to be loaded primarily in longitudinal bending, consistent with the parasagittal orientation of the lower limb (Alexander et al, 1979b;Biewener, 1982;Cubo and Casinos, 1998;de Margerie et al, 2005). However, as noted above, the results here show that the emu femur and TBT are predominantly loaded in torsion.…”
Section: Torsion Versus Axial Loading In Tetrapod Hindlimb Bonessupporting
confidence: 70%
“…Instead, avian hindlimb bones have often been assumed to be loaded primarily in longitudinal bending, consistent with the parasagittal orientation of the lower limb (Alexander et al, 1979b;Biewener, 1982;Cubo and Casinos, 1998;de Margerie et al, 2005). However, as noted above, the results here show that the emu femur and TBT are predominantly loaded in torsion.…”
Section: Torsion Versus Axial Loading In Tetrapod Hindlimb Bonessupporting
confidence: 70%
“…Bars ÂŒ 200 lm (a, d), 2 mm (b, c, e-g) posthatch development cannot be simply extrapolated to the embryonic TMT skeleton, and a relationship between bone porosity and deposition rates has still remained controversial (Starck and Chinsamy, 2002). However, because bone growth requires sufficient nutrient and mineral supplies from dense vascular network (de RicqlĂ©s et al, 1991) and the porosity of bone reflects the degree of bone vascularization (de Margerie et al, 2005), it may be worth considering the relation of growth progression and three-dimensional orientation of channels in which vascular network resides. Our SEM observations showed that the formation of bony struts and trabeculae resulted in the layered arrays of channels in the cylindrical bone wall.…”
Section: Discussionmentioning
confidence: 99%
“…Because locomotion is one of the most frequent and demanding behaviors in which limbs are used (Biewener, 1990;Biewener, 1993), this diversity in limb design is frequently attributed to variation in the mechanical loads that bones experience during locomotion (Currey, 1984;Bertram and Biewener, 1988;Blob, 2001;Currey, 2002;Lieberman et al, 2004;de Margerie et al, 2005). Damage or fracture of bones during locomotion could have serious, even fatal, consequences for animals.…”
Section: Introductionmentioning
confidence: 99%